Phytoplankton Composition of Sematan estuary, Sarawak - Ahmad Akhmal, Bin Atan (Universiti Malaysia Sarawak (UNIMAS), 2014)
Phytoplankton is an autotrophic component of plankton that drifts in both freshwater and marine environments. Proliferation of some phytoplankton species resulted in Harmful Algal Blooms (HABs). This is a phenomenon which the bloom of toxic or harmful phytoplankton responsible death of aquatic life, destruction of marine ecosystem and seafood unsafe for consumption. The mechanism of this organism to proliferate in the estuarine areas has not been well studied and fully understood. A study was conducted to determine the composition of phytoplankton at Sematan estuary in Lundu, Sarawak. Both qualitative and quantitative phytoplankton samples were collected monthly from September 2013 until March 2014. Fourteen taxa of phytoplankton were identified to generic level and the dominant group was diatoms. The dominance diatoms were Coscinodiscus and Pleurosigma. Physical parameters showed weak relationship with cell density except for transparency while the macronutrients, all of the parameters have weak impact towards the cell density. There were 6 HABs genera found which were Ceratium, Chaetoceros, Odontella, Rhizosolenia, Thalassionema and Nitzschia. However, more sampling should be done in order to get more accurate data.